ChemInform Abstract: β‐Xylopyranosides: Synthesis and Applications. Issue 1 (17th December 2015) - Brusa, Charlotte; Muzard, Murielle; Remond, Caroline; Plantier‐Royon, Richard
Abstract: Review: 260 refs.